Pengaruh Koneksi Politik, Capital Intensity, Dan Leverage Terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019- 2023) - Khasanah, Istifatul (Business and Accounting Education Journal, 2025)
This study aims to determine the effect of political connections, capital intensity, and leverage on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange during 2019-2023. The independent variables in this study include political connections, capital intensity, and leverage while the dependent variable is tax aggressiveness as measured using the Effective Tax Rate (ETR). The data used in this study are secondary data. The population and sample in this study were all manufacturing companies listed on the IDX whose samples totaled 75 observations. The sample selection method uses purposive sampling method with panel data analysis. The results showed that political connections and capital intensity have no effect on tax aggressiveness, while leverage has a positive effect on tax aggressiveness.